Understanding weather and climate - Aguado, Edward (Pearson, 2015)
Understanding Weather and Climate illustrates meteorology and climatology using everyday occurrences and inspired technology tutorials to engage students in learning about atmospheric processes and patterns. The Seventh Edition extends coverage of global climate change with new and unique sections covering oceans and climate in the Earth system. Each chapter also focuses on the human aspect of weather and climate, covering high interest weather-related hazards that draw students into the course, while incorporating the latest science and the most relevant issues.